2023
DOI: 10.20517/cdr.2022.136
|View full text |Cite
|
Sign up to set email alerts
|

Review of 5-FU resistance mechanisms in colorectal cancer: clinical significance of attenuated on-target effects

Abstract: The emergence of chemoresistant disease during chemotherapy with 5-Fluorouracil-based (5-FU-based) regimens is an important factor in the mortality of metastatic CRC (mCRC). The causes of 5-FU resistance are multi-factorial, and besides DNA mismatch repair deficiency (MMR-D), there are no widely accepted criteria for determining which CRC patients are not likely to be responsive to 5-FU-based therapy. Thus, there is a need to systematically understand the mechanistic basis for 5-FU treatment failure and an urg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 132 publications
0
8
0
Order By: Relevance
“…5-FU, an early-reported chemotherapeutic drug, remains a cornerstone in the systemic treatment of CRC. Despite advancements in cancer treatment, the prognosis of CRC patients receiving 5-FU therapy remains unsatisfactory [ 32 ]. Therefore, it is crucial to explore and enhance the sensitivity of 5-FU to better design appropriate treatment strategies and achieve personalized care that effectively improves patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…5-FU, an early-reported chemotherapeutic drug, remains a cornerstone in the systemic treatment of CRC. Despite advancements in cancer treatment, the prognosis of CRC patients receiving 5-FU therapy remains unsatisfactory [ 32 ]. Therefore, it is crucial to explore and enhance the sensitivity of 5-FU to better design appropriate treatment strategies and achieve personalized care that effectively improves patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Given the important toxicity of these treatments, identifying those patients is very important in order to improve their quality of life and prevent their exposure to a medication with limited interest and high toxicity for them. We found that one of the genes most associated and predictive of the CIMP phenotype is TYMS (thymidylate synthase), which has been shown to be up-regulated by Myc [ 41 ] and to drive resistance to 5-FU treatments, although it is the target of the drug [ 42 , 43 ]. Hence, since the 1C-metabolism pathway seems to play a central role in CIMP tumours, other targets in the pathway should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance is estimated to occur in 90% of metastatic CRC cases [124]. The possible mechanisms of resistance to 5-FU are complex and varied and have been described extensively in the literature [124][125][126]. The most common are changes in the expression of genes encoding enzymes involved in the metabolism of 5-FU, particularly the upregulation of thymidylate synthase, the main enzyme [127].…”
Section: Simultaneous Stimulation With Thymoquinone and Known Chemoth...mentioning
confidence: 99%